The effect of conservation agriculture technologies adoption on food production and security in Northern Malawi: evidence from Mzimba district - Munthali, George N. Chidimbah; Puming, He; Banda, Lazarus Obed Livingstone; Ngulube, Peter Stephen Donald; Daru, Gama Rivas; Mzumara, Thokozani; Chitete, Moses M. N.; Jere, Zondiwe Mabilabo (Frontiers in Nutrition, 2025)
BackgroundAdoption of conservation agriculture technologies (CATs) has emerged as a strategy to improve farm productivity and achieve food security in many parts of the world.AimThis study aimed to assess the effect of CAT adoption on food production and security.MethodsThis quantitative cross-sectional study was conducted in the Vibangalala Extension Planning Area (EPA) in Mzimba district, Northern Malawi. Data was collected using structured questionnaires. The data were entered in SPSS version 27. Descriptive statistics included frequency, percentage, weighted percentage, means, standard deviations, and standard error mean. Inferential statistics included a t-test and a linear regression model, with the value of p < 0.05 considered statistically significant.FindingsThe study found that households that adopted CATs have high food production and experience food security compared to non-adopters. Adoption of CATs significantly boosts production, with adopters experiencing lower food insecurity and better dietary diversity than non-adopters.Conclusion and recommendationThe study confirms that adopting conservation agricultural technologies is integral to improving agricultural production, but remains entangled in disparities related to gender, farm size, and education. Efforts should be made to ensure equity and equality in conservation agricultural technology adoption to improve food security for all.